Phase III safety study of rituximab administered as a 90-minute infusion in patients with previously untreated diffuse large B-cell and follicular lymphoma. Issue 10 (October 2014) - Dakhil, Shaker; Hermann, Robert; Schreeder, Marshall T.; Gregory, Stephanie A.; Monte, Marc; Windsor, Kevin S.; Hurst, Deborah; Chai, Akiko; Brewster, Michael; Richards, Paul
Abstract This phase III, multicenter, single-arm trial investigated the impact of 90 min rituximab infusions on infusion-related reactions (IRRs) in patients with untreated diffuse large B-cell lymphoma (DLBCL) or follicular lymphoma (FL). Patients received six or eight cycles of rituximab plus cyclophosphamide, vincristine, doxorubicin and prednisone for DLBCL or plus cyclophosphamide, vincristine and prednisolone for FL. A total of 425 patients received the first rituximab infusion per standard guidelines; median duration 240 min. Patients who did not experience grade ≥ 3 IRRs received subsequent infusions over 90 min (363 patients). A total of 303 patients received ≥ 6 cycles of rituximab. Fifty-three patients withdrew after cycle 1; 10 for grade 3 or 4 IRRs and one for a grade 3 adverse event. During cycle 2, 139 patients had IRRs, including four grade 3 IRRs. A 90 min rituximab infusion is well tolerated and feasible for patients with DLBCL or FL who tolerate the first standard rate infusion.